On the Reactivity of N-tert-Butyl-1,2-Diaminoethane: Synthesis of 1-tert-Butyl-2-Imidazoline, Formation of an Intramolecular Carbamate Salt from the Reaction with CO2, and Generation of a Hydroxyalkyl-Substituted Imidazolinium Salt - Kieren J. Evans; Ben Potrykus; Stephen M. Mansell (Heteroatom Chemistry)
N-tert-Butyl-1,2-diaminoethane was shown to react rapidly with atmospheric carbon dioxide to generate the zwitterionic ammonium carbamate salt CO2N(H)C2H4N(H)2tBu (1). Reaction of N-tert-butyl-1,2-diaminoethane with triethylorthoformate gave 1-tert-butyl-2-imidazoline (2) in 24% yield after fractional distillation, and the hydroxyalkyl-tethered imidazolinium salt [HOC(Me)2CH2NC2H4N(CH)tBu][Cl] (3) was synthesised from the sequential reaction of N-tert-butyl-1,2-diaminoethane with isobutylene epoxide, HCl, and triethylorthoformate.